Noble gas and neuroprotection: From bench to bedside - Yin, Haiying; Chen, Zijun; Zhao, Hailin; Huang, Han; Liu, Wenwen (Frontiers in Pharmacology, 2022)
In recent years, inert gases such as helium, argon, and xenon have gained considerable attention for their medical value. Noble gases present an intriguing scientific paradox: although extremely chemically inert, they display a remarkable spectrum of clinically useful biological properties. Despite a relative paucity of knowledge about their mechanisms of action, some noble gases have been used successfully in clinical practice. The neuroprotection elicited by these noble gases has been investigated in experimental animal models of various brain injuries, such as traumatic brain injury, stroke, subarachnoid hemorrhage, cerebral ischemic/reperfusion injury, and neurodegenerative diseases. Collectively, these central nervous system injuries are a leading cause of morbidity and mortality every year worldwide. Treatment options are presently limited to thrombolytic drugs and clot removal for ischemic stroke, or therapeutic cooling for other brain injuries before applying noble gas. Currently, there is increasing interest in noble gases as novel treatments for various brain injuries. In recent years, neuroprotection elicited by particular noble gases, xenon, for example, has been reported under different conditions. In this article, we have reviewed the latest in vitro and in vivo experimental and clinical studies of xenon, argon, and helium actions, and discuss their potential use as neuroprotective agents.